Familial Prevalence of Inflammatory Bowel Disease in Northern Alberta - BR Pinchbeck; J Kirdeikis; ABR Thomson (Canadian Journal of Gastroenterology)
Previous studies have reported a high prevalence of inflammatory bowel disease among the relatives, and especially siblings, of patients with Crohn's disease or ulcerative colitis. This high familial prevalence of Crohn's disease and ulcerative colitis suggests that genetic factors could play a role in the development of these disorders. The present study attempted to assess the relative risk for relatives of Crohn's disease and ulcerative colitis patients based on data provided by 1015 questionnaires completed by patients in northern Alberta. A Mx2 2x2 test among relatives was performed on the diseased versus normal data for each diagnosis to determine if significant differences existed. The prevalence for mothers and sisters was the highest of the relative groups for Crohn's disease ( 6430 of 105 and 4670 of 105 , respectively). Female relatives tended to have twice the prevalence of their male counterparts. There were differences between mother, daughter and sister prevalence rates for Crohn's disease. These results support the hypothesis that a genetic predisposition in families combined with possible environmental and lifestyle influences determine the relative risk of developing Crohn's disease and ulcerative colitis.